Средства защиты рук рабочих на машиностроительных предприятиях - Цуцков М. Е. Михаил Егорович; Ардасенов В. Н. Валерий Николаевич; Брайнина М. Л. Маргарита Леонидовна; Шаркова В. В.; Шумяцкая Т. Н. (Москва, Машиностроение, 1983)
Авт. указаны на обороте тит. л.